On the equivalence of the forecast value construction in the “pyramidal” extrapolation method and cubic forecast (Моделювання, керування та інформаційні технології, 2020)
The paper is devoted to the new method of short time series extrapolation, which was developed in recent years and was called “pyramidal”. This method can be used for predicting the deterministic component of an arbitrary economic, environmental and geophysical parameters. Numerical results show significant advantages of the proposed method in comparison with approaches to extrapolate, based on the use of polynomials, including Newton’s extrapolation . In this paper we study the procedure for constructing the forecast value in accordance with the pyramidal method and show that it is equivalent to the cubic forecast.